2019
DOI: 10.5796/electrochemistry.18-00084
|View full text |Cite
|
Sign up to set email alerts
|

Highly Safe 100-Wh-class Lithium-ion Battery Using Lithium Bis(trifluoromethanesulfonyl)amide-Tetraethylene Glycol Dimethyl Ether Equimolar Complex-based Quasi-solid-state Electrolyte

Abstract: A highly safe 100 Wh-class laminated lithium ion battery (LIB) was developed. For ensuring safety of the LIB, a liquid electrolyte was quasi-solidified at silica surfaces. For the liquid electrolyte, a solvate ionic liquid (SIL), which is an equimolar complex of lithium bis(trifluoromethanesulfonyl)amide (LiTFSA) and tetraethylene glycol dimethyl ether (G4), Li(G4)TFSA, was used. For enhancing discharge-rate capability, Li(G4)TFSA was diluted by propylene carbonate (PC). Then, for enhancing cycle life, vinylen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
26
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(26 citation statements)
references
References 42 publications
0
26
0
Order By: Relevance
“…6 The high mechanical strength of the present MLS-based colloidal gel electrolytes may also contribute to the above appealing features in battery systems. The silica-based quasi-solid electrolytes containing the MLSs can indeed be employed for highly safe 100 Wh-class allsolid state Li-ion batteries, as demonstrated by Unemoto et al 31 Figure 3 displays the V silica -dependence of the shear thickening behavior for the [BF 4 ]-based MLS-silica composites. With increasing V silica , the maximum peak viscosity increased and the critical shear rate, at which the viscosity starts to increase, systematically shifted to a lower shear rate for both systems.…”
Section: Resultsmentioning
confidence: 88%
“…6 The high mechanical strength of the present MLS-based colloidal gel electrolytes may also contribute to the above appealing features in battery systems. The silica-based quasi-solid electrolytes containing the MLSs can indeed be employed for highly safe 100 Wh-class allsolid state Li-ion batteries, as demonstrated by Unemoto et al 31 Figure 3 displays the V silica -dependence of the shear thickening behavior for the [BF 4 ]-based MLS-silica composites. With increasing V silica , the maximum peak viscosity increased and the critical shear rate, at which the viscosity starts to increase, systematically shifted to a lower shear rate for both systems.…”
Section: Resultsmentioning
confidence: 88%
“…Furthermore, the use of suitable additives remarkably enhanced the electrode passivation behavior, leading to promising cell performances. Indeed, literature works have shown that vinylene carbonate (VC), fluoroethylene carbonate (FEC), and lithium nitrate (LiNO 3 ) may improve the SEI between anode and electrolyte. In particular, it is widely demonstrated that LiNO 3 ‐containing electrolytes may form a uniform and stable anode passivation layer containing both organic ( e.g ., ROLi and ROCO 2 Li) and inorganic ( e.g ., Li x NO y , Li 3 N, and Li 2 O) species, which can mitigate the parasitic reactions in the cell and limit the lithium dendrite growth .…”
Section: Introductionmentioning
confidence: 99%
“…However, the application of such extras compromises the volumetric energy density of the battery pack. 2 Ensuring high thermal stability and high safety of the cells by means of constituent materials enables the cooling parts and extra spaces to be eliminated, thus leading to an enhanced volumetric energy density of the battery pack.…”
mentioning
confidence: 99%
“…In addition, SIL can be quasi-solidified through its interaction with the oxide surfaces. 2,6,7 A quasi-solidstate electrolyte (QSE) prepared by mixing of the SILs with oxide particles, and fixing them with a polytetrafluoroethylene (PTFE) binder enables the liquid phase to be stored at high concentration. For example, when Li(G4)TFSA is mixed with fumed silica nanoparticles with a 7 nm diameter, the QSE can contain 80% of the electrolyte while remaining in a self-standing sheet.…”
mentioning
confidence: 99%
See 1 more Smart Citation